Answer:
Therefore,
![f(-2)=-11\\f(0)=5](https://img.qammunity.org/2021/formulas/mathematics/middle-school/r504q15jbsvf9fdebgt3127ypqjez9kica.png)
Explanation:
Function:
A function is like a machine that gives an output for a given input.
A function has an independent variable which is called the input of the function.
The output for a given input is called the dependent variable.
Here. 'z' is the input independent variable
f(z) is the function dependent variable i.e function of z as an output.
Here,
![f(z)=5-4z^(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/q4ztiu4ltf7fz4mec1iognj3vmb44qcoal.png)
Therefore, at z = -2 we have
![f(-2)=5-4(-2)^(2)=5-4(4)=5-16=-11\\\\f(-2)=-11](https://img.qammunity.org/2021/formulas/mathematics/middle-school/t1dtq1sb1ybtl9i72bhbhlfref17pn0chk.png)
Similarly at z =0 we have
![f(0)=5-4(0)^(2)=5-0=5\\f(0)=5](https://img.qammunity.org/2021/formulas/mathematics/middle-school/wh1mdtoxasq7xn98mnljulf24hyu39jf7s.png)
Therefore,
![f(-2)=-11\\f(0)=5](https://img.qammunity.org/2021/formulas/mathematics/middle-school/r504q15jbsvf9fdebgt3127ypqjez9kica.png)